Collembola of the Campanet cave (Mallorca, Balearic Islands), with descriptions of new species of Pseudosinella (Entomobryidae) and Oncopodura (Oncopoduridae) - Seminario-Córdova, Renzo A.; Baquero, Enrique; Jordana, Rafael; Vadell, Mateo (Zootaxa, 2018)
This paper documents the collembolan fauna of the Campanet cave, in the province of Mallorca (Balearic Islands). Sampling was carried out using pitfall traps baited with beer and checked every 15 days. The cave fauna included the following species: Coecobrya tenebricosa, Disparrhopalites patrizi, Entomobrya pazaristei, Neelus murinus and Dicyrtomina ornata. In addition, two new species were found and are described here: Pseudosinella grauae sp. nov. and Oncopodura siquierae sp. nov. The former is characterised by an unpigmented body, eyes absent, dorsal chaetotaxy R0R1R2001/31/0101+2, with accessory chaeta ‘s’ on Abd IV; all claws with three teeth; posterior chaetae on labial triangle as M1, M2, r, E, L1, L2, all ciliated except for r, a smooth microchaetae and smooth remaining anterior labial chaetae. O. siquierae sp. nov is typified by an unpigmented body; eyes absent; PAO as a single small vesicle; Ant IV with four distal leaf‑shaped sensilla and a basal pointed cylindrical chaeta; dens with one proximal inner spine, one distal inner tooth and a large disto-external hook‑like spine; and mucro with four teeth, the basal one distinctly pointed.